MANAJEMEN PENGELOLAAN BADAN USAHA MILIK DESA (BUMDes) BERBASIS POTENSI LOKAL DI DESA PASIRAMA KIDUL KECAMATAN PEKUNCEN KABUPATEN BANYUMAS - Paulus Israwan Setyoko; Denok Kurniasih (PARADIGMA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Rural development can be increased through developing village economic potential and becoming a joint forum for rural communities in developing themselves and their environment independently and participatively. The village community has the same rights to participate in growing and developing in building a life order and prosperity equally. One of the new approaches that is expected to be able to become a driving force for development and the wheel of the village economy is through the establishment of rural community economic institutions known as Village Owned Enterprises (BUMDes) as one of the mainstay programs in increasing village economic independence. This service activity aims to analyze and describe in depth the Management of Village Owned Enterprises (Bumdes) in Pasiraman Kidul Village, Banyumas District. After analyzing the problem, aspects of BUMDes institutional assistance activities can be determined. Asepk which is the focus of the implementation of this community service focuses on organizational management which sees BUMDes development from the aspects of planning, organizing, directing and controlling in carrying out the functions and responsibilities of managing village-owned enterprises (BUMDes).